PENAMBAHAN ENZIM CAIRAN RUMEN LIMBAH RUMAH POTONG HEWAN PADA PAKAN BERBASIS WHEAT POLLARD DENGAN PROSES PENGOLAHAN PADA KOMPOSISI KIMIA PAKAN - Dadik Pantaya., dkk (BPPT)
The present study was conducted to clarify the effect of addition of enzymes from rumen liquor on performance broiler of pelleting feed with basal ration of wheat pollard with addition of enzymes and processing broiler diets. Ruminal enzymes were extracted from Australian Commercial Cross (ACC) cattles. Application of enzyme on wheat pollard. Enzyme was reacted with wheatpollard and mixed with another feedstuff before steam pelleting process. The combination nine experimental diets were used as follows three levels enzyme supplementation (0, 620 and 1.240 U/kg) and three levels steam temperature at (60, 80 and 100 oC) Feed particles size, hardness, PDI (Pellet Durability Index), moisture content, protein, GE and hemicellulosa were evaluated parameter devided into nine treatmens were used in this research. Data from Completely Randomized Design factorial 3 x 3 were analyzed with Anova, if differences were continued by Duncan’s new multiple range test. Enzyme supplementation decreased feed hardness and PDI. There were interaction beetwen enzyme and temperature for feed moisture content. Hemicellulosa was significantly reduced by steam temperature at 80 and 100 oC and enzyme supplementation 1.240 U/kgKey Words: enzyme liquor rumen, wheat pollard, steam pelleting, feed Chemical composition